2008
DOI: 10.1128/jvi.01181-08
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Simian Immunodeficiency Virus SIV SM /Human Immunodeficiency Virus Type 2 Vpx Function in Human Myeloid Cells

Abstract: Human immunodeficiency virus type 2 (HIV-2)/simian immunodeficiency virus SIV SM Vpx is incorporated into virion particles and is thus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
140
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(157 citation statements)
references
References 49 publications
(89 reference statements)
16
140
1
Order By: Relevance
“…Knockdown of DCAF-1 was achieved upon transduction of target cells with lentiviral vectors encoding control or DCAF-1 hairpins (22). Briefly, lentivectors were produced by cotransfection of HIV-1 Gag-Pol, VSV-G, and the indicated short hairpin RNA (shRNA) constructs as described previously using the following target sequences: for ShDCAF-1, GCGGACTGGAGGTGATCAT; and for ShControl, AGC TCCCGTGAATTGGAATCC.…”
Section: Methodsmentioning
confidence: 99%
“…Knockdown of DCAF-1 was achieved upon transduction of target cells with lentiviral vectors encoding control or DCAF-1 hairpins (22). Briefly, lentivectors were produced by cotransfection of HIV-1 Gag-Pol, VSV-G, and the indicated short hairpin RNA (shRNA) constructs as described previously using the following target sequences: for ShDCAF-1, GCGGACTGGAGGTGATCAT; and for ShControl, AGC TCCCGTGAATTGGAATCC.…”
Section: Methodsmentioning
confidence: 99%
“…This restriction factor was identified based on studies showing that certain strains of lentiviruses that encode the auxiliary protein Vpx can bypass the block to viral replication in myeloid cells [21,32]. SAMHD1 was recovered in biochemical purification of Vpx and its associated cofactors and was identified as the restriction factor operating in myeloid cells [6,7].…”
Section: Samhd1 As An Exception?mentioning
confidence: 99%
“…Until recently most of the studies involving lentiviruses as tools to transfer genes into human DCs reported the use of Vpr/Vpxencoding SIV-derived or HIV-1-based vectors transcomplemented with Vpr/Vpx-encoding VLPs (8,40,42,43,51,59,74). Vpx is an accessory protein from SIV and HIV-2 viruses known to enable the inhibition of a host defense mechanism against infection, depending in part on the Cul4-based E3 ubiquitin ligase complex (40,43).…”
Section: Discussionmentioning
confidence: 99%
“…Vpx is an accessory protein from SIV and HIV-2 viruses known to enable the inhibition of a host defense mechanism against infection, depending in part on the Cul4-based E3 ubiquitin ligase complex (40,43). Vpx has been recently described as an interactant of the cellular host protein SAMHD1 identified as a major restriction factor of the transduction of myeloid cells by HIV-1-based viruses (47,54).…”
Section: Discussionmentioning
confidence: 99%